Pattern of Chest Pain in Long COVID Syndrome (Green Life Medical College Journal, 2025)
Introduction: The COVID-19 pandemic has persisted for over four years, resulting in numerous complications, including myocardial infarction, stroke, heart failure, and thromboembolism. These occur via various mechanisms, such as endothelitis, multisystem inflammatory syndrome, cytokine storm, and activation of the coagulation cascade. Despite recovery, many patients experience persisting symptoms, including chest pain and fatigue. However, the specific complications that arise and their underlying causes remain largely unclear. This study aimed to examine the frequency and pattern of chest pain in this population and thus unveiling the underlying pathophysiology. Methods: This is an uni-center, prospective observational cohort study, conducted in Department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), from July 2021-June 2023. Patients presenting within 7 days of positive RT-PCR COVID-19 report, were screened for this study. Among them, 382 patients were enrolled in the study, following inclusion and exclusion criteria. Relevant history (breathlessness, chestpain, palpitation, ankle edema, syncope,pulse, BP, JVP, lungbase, edema, NYHA Class, 6MWD) & cardiac investigations (Trop I, NT Pro-BNP, S.Creatinine, S.Electrolytes, S.Albumin, S.TSH, CBC, CRP, CXR, ECG, Echocardiography) were done at baseline. Patients were followed up in Cardiology OPD Clinic,BSMMU, after 3 months of enrollment, with same clinical, laboratory and cardiac investigations. Data were collected in a semi structured data sheet via personal interview. The variables included were, age, sex, chest pain, palpitation, breathlessness, ankle edema, syncope, pulse, systolic and diastolic blood pressure, raised JVP, lung base crackles and functional capacity (NYHA Classification and 6 Minute Walk Distance), S. Troponin-I, S. NT-proBNP, S. Creatinine, S. Albumin, TSH,FT4, CXR P/A view, ECG, Resting Transthoracic Echocardiography. Data analysis was done using IBM SPSS® 29.0. Results: The study showed, 59% of the populations presented with cardiac symptoms at 3 months follow up. Most of the symptomatic populations were between 60-69 years of age, male were more affected than female. Commonest cardiac manifestation were palpitation (79%), chest pain (53%) & breathlessness(48%). Chest pain was due to unstable angina (70%) and myocardial infarction (30%). Conclusion: At the end of 3 months, a significant proportion of Long COVID-19 patients developed cardiac symptoms, specially chest pain due to coronary artery disease. So, further research in the field of Long COVID-19 is necessary to find out further impacts of this condition on cardiovascular syste.Green Life Med. Col. J. 2025; 10(1): 3-7